The coatings in manufacturing engineering selected, peer reviewed papers from the 8th International Conference on THE coatings in Manufacturing Engineering, Erlangen-Germany, April 14-15, 2010 - Bach, Friedrich-Wilhelm (Trans Tech, 2010)
Coating technology has made great strides during recent years. The properties of surface layers determine the function and quality of entire components. Thus, it is essential to obtain information concerning the development and functionality of the topmost layers. The beneficial effect of coating technology can be observed in many manufacturing fields, where it solves problems such as wear, corrosion, erosion, electrical contact, etc. Even decoration falls under this heading. The 28 peer-reviewed papers are grouped into chapters: tools session, properties session, test / simulation session, coatings session, tribology session. Overall, the contents provide a timely insight into the subject.
Conference alternates location among THE--Thessaloniki, Greece and Hannover and Erlangen, Germany.
Keywords: Coatings -- Congresses.; elektronické knihy; electronic books